PENGGUNAAN DANA BANTUAN PROGRAM INDONESIA PINTAR (PIP) OLEH SMK DI KOTA SURAKARTA - Fika Khoirunisa, Fika; Nurhadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education plays an important role in overcoming poverty, because it can improve the quality of human resources and the welfare of the nation. The Program Indonesia Pintar (PIP) is one of the government's initiatives to help students from underprivileged families in meeting their educational needs. This study aims to analyze the utilization of PIP funds by students at SMKN Surakarta. This study uses a qualitative descriptive approach with interviews as a data collection technique. The research informants consisted of 48 students receiving PIP funds at SMKN Surakarta. The results showed that most students (81.44%) used PIP funds in accordance with the provisions of Permendikbud No. 19 of 2016, especially to buy books and stationery, and other school supplies. A small number of students also used funds for non-educational purposes such as pocket money and transportation. These findings indicate that the PIP program at SMKN Surakarta has helped students in meeting their educational needs, although there are still some recipients who do not fully utilize the funds in accordance with applicable regulations.